Analysis of Armed Separatist Movement Conflict in Casamance, Senegal & Lessons Learned for the Indonesian Government in Addressing Similar Conflicts - Sakinatunnafsih Anna; Anang Puji Utama; Bayu Setiawan; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
This in-depth article explores the complex factors that have contributed to the long-standing armed separatist conflict in Casamance, Senegal. It offers an analysis of the most effective approaches to resolving the conflict, drawing valuable lessons that can be applied to other nations grappling with similar challenges. Historical, socio-economic, political, and cultural factors all play a role in the conflict, which has endured for decades. There are additional issues to navigate, including military fragmentation, political leadership voids, economic and cultural decline, failed ceasefires, and neighboring state behavior. By examining these causes and lessons learned, this article provides valuable insights for Indonesia and other nations facing separatist movements. Despite the daunting nature of the conflict, there are several potential solutions that can be employed to facilitate successful negotiations in the future, including trust-building, official and unofficial mediation, the establishment of a State Peace Secretariat in Casamance, and a comprehensive, inclusive settlement negotiation.